International Saleroom - Anonymus, A. (1965)
fig. 3: Rare cylinder seal, with a frieze of cows in the upper register, in the lower a row of reed huts or shrines; from Warka, 3400-3100 B.C. Bought by the Ashmolean Museum, Oxford.